A new species of Valettiopsis Holmes, 1908 (Crustacea: Gammaridea: Lysianassoidea) from abyssal waters off California - Hendrycks, Ed A. (Zootaxa, 2007)
Deep-sea sampling off the central California coast has provided numerous material of a new amphipod species of the genus Valettiopsis Holmes, 1908. Valettiopsis concava sp. nov. is described from abyssal collections taken from baited traps and sponge stalk communities. Morphological characteristics which distinguish the new species from its congeners are found in the dorsal profile of the body, integument surface, and shape of coxa 2 and basis of pereopod 7. This contribution presents the second recorded species of the genus Valettiopsis described from the north Pacific, the first being the type species V. dentata Holmes, 1908. The new species is fully illustrated and compared with related species. The generic identity of Valettiopsis ruffoi Serejo & Wakabara, 2003 is discussed. A key to Valettiopsis species is provided.